EFFECT OF PARASITIC COPEPODS ON THE LENGTH-WEIGHT RELATIONSHIP AND THE CONDITION FACTOR OF CRUCIAN CARP (CARASSIUS CARASSIUS) IN THE BENI-HAROUN DAM, MILA CITY, NORTHEAST ALGERIA - BERROUK, Houda; SID, Abir; LAHOUAL, Ahlem; SAHTOUT, Fatiha; KAOUACHI,Nouha; BOUALLEG, Chahinaiz (My University, 2022)
Ectoparasites are commonly the largest group of fish pathogenic organisms, and among these, crustaceans cause considerable pathogenic effects on farmed freshwater fishes. The present study was undertaken to investigate the effect of parasitic copepods on the growth of Carassuis carassuis, from the Beni-Haroun Dam, Mila city, Northeast Algeria. The study was conducted on 242 fish individuals sampled between July 2015 – October 2016. The sex was macroscopically determined and age was specified by the scalimetry method. The identified gill ectoparasites were six ectoparasitic species belonging to four genera and two families, namely Ergasilus briani, E. megaceros, E. sieboldi, Paraergasilus brevigiditus, Neoergasilus japonicas and Lernea cyprinacea. Further, the fishes growth under the effect of parasitic copepods was carried out by the mathematical method of Von Bertalanffy, and accordingly, the growth parameters in C. carassuis were L∞ = 34.1 cm; K = 0.65; t0 =-1.01; Ø’ = 2.87, in the non-parasitized fishes, and L∞= 29.47 cm; K=0.92; t0= -0.80; Ø’= 2.90, in the parasitized fishes. In addition, the parasites slow down the absolute growth in length of the parasitized fishes which, in turn, suffer from a drop in their condition factor (K = 1.26) compared to the non-parasitized fishes (K = 1.34). The evolution of the total weight of the studied fishes in relation to their length revealed minor allometry (b<3) for the non-parasitized and parasitized fishes (without distinction between the two sexes).